Factors in ProGlide® Vascular Closure Failure in Sheath Arteriotomies Greater than 16 French. (October 2019) - Chen, I-Ming; Lee, Tsung-Hsing; Chen, Po-Lin; Shih, Chun-Che; Chang, Hsiao-Hunag
Abstract : Objectives: The ProGlide® vascular closure device (Abbott Vascular, Redwood City, CA, USA) is approved for the closure of arterial punctures (typically 5–21 Fr sheath; maximum outer diameter, 26 Fr). However, a failure rate of about 2–8% is reported. This study was conducted to analyse factors predisposing to failure when the devices were used for the closure of large hole (16–26 Fr) arteriotomies, and to determine the predictive cut off values of predisposing factors. Methods: In this retrospective study, the ProGlide® device was used to achieve vascular access site closure in 458 patients undergoing repair of abdominal aortic aneurysm, thoracic aortic aneurysm, type B aortic dissection, or transcatheter aortic valve implantation. The primary endpoint was device failure, defined as inability to achieve common femoral artery (CFA) closure; successful repair, development of acute lower limb ischaemia and haemodynamic compromise; or delayed pseudoaneurysm formation during the follow up period, requiring open repair. Results: Overall, ProGlide® failure occurred in 7.6% of cases. Factors that predisposed to failure included a history of peripheral arterial disease (PAD) ( p  < .001), the presence of CFA calcification ( p  < .001), the depth of the skin puncture site ≥ 33 mm ( p  < .001), body mass index (BMI) of ≥28.7 kg/m 2 ( p  < .001), and use of sheath size ≥ 19 Fr ( p  < .001). Conclusion: Factors such as BMI, history of PAD, the presence of CFA calcification, the depth of the skin puncture site, and sheath size are significantly associated with ProGlide® failure. Hence, careful patient and device selection and operating procedure are paramount to achieve successful outcomes.